Usage of HCV viremic organs in liver transplantation to anti-HCV negative recipients: The current status and review of literature - Çiftçibaşı Örmeci, Aslı; Yıldız, Çağla; Saberi, Behnam; Gürakar, Merve; Şimşek, Cem; Gürakar, Ahmet (Turkish Journal of Gastroenterology, 2019)
Liver transplantation is the main curative therapy for end-stage liver disease. The number of transplanted organs is increasing globally. However, the number of available organs in the pool is insufficient, considering the excessive number of patients on the waiting list, which is a major concern for transplant programs. Hepatitis C infection (HCV) is a common indication for liver transplantation, and in recent years, a major progress has been made in its treatment with direct-acting antiviral (DAA) agents. HCV-positive livers have been transplanted to HCV-positive recipients for a long time. The high rate of sustained virologic response through DAA has brought new treatment options for the patients during the pre- and post-transplantation periods. Recently, there have been few reports of transplanting the available HCV-positive organs to HCV noninfected recipients. However, there is not yet an agreement on the optimal selection of patients who would benefit from such transplantation, and this has become a current topic of interest. Thus, we aim to review the current literature on this evolving topic.